Clinical neurology - Greenberg, David A. (McGraw-Hill Medical, 2012)
For more than twenty years, Clinical Neurology has helped students, residents, and clinicians understand the link between basic neuroscience and current approaches in diagnosis and treatment. Distinguished by its practice-oriented approach to neurology based on presenting symptoms, this trusted classic delivers the clearest and most concise introduction to the field available anywhere.